THE PROBLEM OF SUFFERING IN ISLAM - Mahmoud M Ayoub (Journal of Dharma, 2020)
Mankind, from time immemorial, has been wrestling with the problem of suffering. Men and women through the ages have sought answers to this problem through myth and ritual, art and philosophy, religious piety and mysticism. It may be safely said that religious traditions have been, in part, attempts to answer the question of human suffering and to find meaning and purpose in life in spite of it.